Permitido decir “para”: crítica de la perspectiva tradicional frente al problema de la teleología en la enseñanza de la biología - González Galli, Leonardo Martín (Revista Científica, 2019)
In this paper we review the problem of teleological conceptions in the teaching and learning of evolutionary biology. We characterize what we call the “traditional perspective” in relation to this problem and question the epistemological and psychological-didactic assumptions on which it is based. Against this traditional perspective, based on the objective of eliminating teleological reasoning and the censorship of their expressions, we offer an alternative perspective based on the development, on the part of students, of the ability to regulate consciously and intentionally the recourse to teleological reasoning and expressions. We also offer some guidelines for the design of specific teaching activities in relation to this objective.